Dialogue between mitochondria and endoplasmic reticulum-potential therapeutic targets for age-related cardiovascular diseases - Chen, Chen; Dong, Xueyan; Zhang, Wang; Chang, Xing; Gao, Wulin (Frontiers in Pharmacology, 2024)
Mitochondria-associated endoplasmic reticulum membranes (MAMs) act as physical membrane contact sites facilitating material exchange and signal transmission between mitochondria and endoplasmic reticulum (ER), thereby regulating processes such as Ca 2+/ lipid transport, mitochondrial dynamics, autophagy, ER stress, inflammation, and apoptosis, among other pathological mechanisms. Emerging evidence underscores the pivotal role of MAMs in cardiovascular diseases (CVDs), particularly in aging-related pathologies. Aging significantly influences the structure and function of the heart and the arterial system, possibly due to the accumulation of reactive oxygen species (ROS) resulting from reduced antioxidant capacity and the age-related decline in organelle function, including mitochondria. Therefore, this paper begins by describing the composition, structure, and function of MAMs, followed by an exploration of the degenerative changes in MAMs and the cardiovascular system during aging. Subsequently, it discusses the regulatory pathways and approaches targeting MAMs in aging-related CVDs, to provide novel treatment strategies for managing CVDs in aging populations.